European FDI strategies in Mercosur countries - Peter Nunnenkamp (Kiel Institute of World Economics (IfW), 2001)
Mercosur countries have witnessed a boom of foreign direct investment (FDI) inflows since the early 1990s. However, regional integration, viewed in isolation, was not sufficient for the subregion to regain its attractiveness to FDI. FDI growth in individual Mercosur countries was closely related to reform efforts on the national level.The pattern of EU FDI in the subregion reveals some significant changes, notably in terms of its major sources and its sectoral composition. Furthermore, EU investors pursued strategies that differed from those of other foreign investors. Yet, the character of EU FDI has essentially remained unchanged so far. Whether efficiency-seeking FDI by the EU in Mercosur will gain prominence in the future depends critically on Mercosur's trade policy.
Keywords: F36; F21; 330; efficiency-seeking FDI; regional integration; trade policy; EU-Mercosur relations; market-seeking FDI; Direktinvestition; EU-Europäisch; Internationale Markteintrittsstrategie; Standortfaktor; Handelsregionalismus; MERCOSUR-Staaten